Etika Jurnalisme Dalam Pembingkaian Pemulangan WNI Eks ISIS : Analisis Harian Kompas dan Koran Tempo - Ulya, Himmatul (Jurnal Ilmu Komunikasi, 2024)
This research is motivated by the defeat Islamic State of Iraq Suriah (ISIS) which leaves problems for Indonesian former ISIS, which threatens to be stateless. This research wants to show the framing of Indonesian newspapers in reporting on the return of Indonesian citizens who former ISIS to Indonesia from the perspective of journalism ethics, UU Pers No 40/1999 and the social responsibility of the press to the public. The subject of this research is Harian Kompas and Koran Tempo. This research used Zhongdang Pan and Gerald Kosicki's framing analysis method which assumes that every piece of news has a frame that functions as the center of idea organization. The results of this research show significant differences between Harian Kompas and Koran Tempo in framing the repatriation of Indonesian citizens who have been former ISIS. Harian Kompas uses security logic in each of its reports by applying journalism ethics through an approach Utilitarianism by Jeremy Bentham. While Koran Tempo uses humanist logic by applying journalism ethics through the golden rule approach or the reverse.